An updated list of leaf-nosed bats (Hipposideridae) from Vietnam and key features of Hipposideros alongensis - Thong, Vu Dinh (Academia Journal of Biology, 2013)
This paper provided a review of leaf-nosed bats (Hipposideridae) from Vietnam and important characteristics of a Vietnamese endemic bat species. In previous publications including bats of Vietnam, records of four species (Hipposideros bicolor, H. fulvus, H. turpis, Paracoelops megalotis) resulted from improper identification. Without doubt, records of Hipposideros turpis from Vietnam resulted from misidentification of materials of Ha Long Leaf-nosed Bat (Hipposideros alongensis), an endemic bat species to Vietnam. Its external features are similar to those of Horsfield's Leaf-nosed Bat (Hipposideros larvatus). However, Ha Long Leaf-nosed Bat and Horsfield's Leaf-nosed Bat are distinguished by body size, molecular data, and echolocation frequency. On the other hand, H. alongensis comprises two distinct subspecies: Bourret’s Leaf-nosed Bat (H. a. alongensis) and Sung’s Leaf-nosed Bat (H. a. sungi). Of which, H. a. sungi distributes in two national parks (Cuc Phuong and Ba Be) and two nature reserves (Huu Lien and Na Hang) whereas H. a. alongensis distributes in two national parks (Cat Ba and Bai Tu Long) and other islands within Ha Long Bay.